Scaffolds of PCL combined to bioglass: synthesis, characterization and biological performance - da Fonseca, Gabriela Fernandes [UNESP]; Avelino, Sarah de Oliveira Marco [UNESP]; Mello, Daphne de Camargo Reis [UNESP]; do Prado, Renata Falchete [UNESP]; Campos, Tiago Moreira Bastos; de Vasconcellos, Luana Marotta Reis [UNESP]; de Sousa Trichês, Eliandra; Borges, Alexandre Luiz Souto [UNESP] (Springer Nature, 2020)
Biomaterials may be useful in filling lost bone portions in order to restore balance and improve bone regeneration. The objective of this study was to produce polycaprolactone (PCL) membranes combined with two types of bioglass (Sol–Gel and melt-quenched) and determine their physical and biological properties. Membranes were produced through electrospinning. This study presented three experimental groups: pure PCL membranes, PCL-Melt-Bioglass and PCL-Sol-gel-Bioglass. Membranes were characterized using Scanning Electron Microscopy, Fourier Transform Infrared Spectrophotometry (FTIR), Energy-Dispersive Spectroscopy and Zeta Potential. The following in vitro tests were performed: MTT assay, alkaline phosphatase activity, total protein content and mineralization nodules. Twenty-four male rats were used to observe biological performance through radiographic, fracture energy, histological and histomorphometric analyses. The physical and chemical analysis results showed success in manufacturing bioactive membranes which significantly enhanced cell viability and osteoblast differentiation. The new formed bone from the in vivo experiment was similar to that observed in the control group. In conclusion, the electrospinning enabled preparing PCL membranes with bioglass incorporated into the structure and onto the surface of PCL fibers. The microstructure of the PCL membranes was influenced by the bioglass production method. Both bioglasses seem to be promising biomaterials to improve bone tissue regeneration when incorporated into PCL. [Figure not available: see fulltext.].